DIAGNOSIS DAN PENATALAKSANAAN PNEUMONITIS HIPERSENSITIVITAS - Dary, I Wayan; Ngurah Rai, Ida Bagus (journal of internal medicine, 2012)
Hypersensitivity pneumonitis (HP), or extrinsic allergic alveolitis, is a group of immunologically mediated lung diseases in which the repeated inhalation of certain finely dispersed antigens of a wide variety, mainly including organic particles or low molecular weight chemicals, provokes a hypersensitivity reaction with granulomatous inflammation in the distal bronchioles and alveoli of susceptible subjects. HP can be classified as acute, subacute, and chronic form. Clinically its presented as fever, fatique, myalgia, cough and shortness of breath after exposured and physical finding with fever, takipneu, diffuse rhales bibasal. Chest radiograph showed diffuse micronodular pattern or ground-glass appearance on lower and mid field lung only found on ten perse10%n of cases. HRCT can show more specific abnormalities of the lung. Lung function test describe restrictive type. Hystopathologic features are noncaseating granulomas, giant cells with a lot of nucleus, and mononuclear cells infiltration. The most diagnostic criteria used is made by Richerson et al. the history and physical findings and pulmonary function tests indicate an interstitial lung disease, the X-ray film is consistent, there is exposure to a recognized cause, and there is antibody to that antigen. Being an immune reaction in the lung, the most obvious treatment of HP is avoidance of contact with the offending antigen. Systemic corticosteroids represent the only reliable pharmacologic treatment of HP but do not alter the long-term outcome. On the acute HP, prednisone administrate 1 mg/kgBW/day or its equivalent dose for 7 ? 14 days than tapering off foe 2 ? 6 weeks.
Keywords: hypersensitivity pneumonitis, criteria, cortocosteroid